Physical Activity and Mental Health: A Cross-sectional Study of Canadian Youth - Zulyniak, Sara (J Can Acad Child Adolesc Psychiatry, 2020)
OBJECTIVE: Our objective was to examine the associations between recreational and non-recreational physical activity with mental health outcomes among Canadian youth aged 12–17. METHODS: Cross-sectional data from the 2015/2016 Canadian Community Health Survey was used for analysis. Physical activity was classified as either recreational or non-recreational. Both types of physical activity were categorized using the Canadian Physical Activity Guidelines. Mental health outcomes included the Patient Health Questionnaire-9 (PHQ-9) scale dichotomized with 5+ and 10+ cut-offs, self-perceived mental health, and self-reported professionally diagnosed mood and anxiety disorders. Descriptive statistics (proportions with 95% confidence intervals), and multivariable logistic regression were used in the analysis. RESULTS: It was found 21.20% of youth were not participating in recreational physical activity and 40.97% were engaging in below guideline recreational physical activity. No activity, or below guideline recreational physical activity was associated with negative mental health. Non-recreational physical activity models were generally non-significant. Additionally, it was determined that associations between recreational physical activity and PHQ-9 score were only evident in males. For the no activity and below guideline activity levels the odds ratios (ORs)=2.57 and 3.19 for males and OR=0.95 and 0.96 for females, respectively. CONCLUSIONS: Recreational physical activity is associated with youth mental health (particularly in males), but non-recreational physical activity is not consistently associated. While the data are cross-sectional and cannot support causal inference, these results highlight the potential importance of accessible recreational physical activity programs. Further, these results may inform guidelines about types of youth physical activity and their apparent mental health benefits.